Phenanthrenes from Juncus atratus with antiproliferative activity. Issue 1 (3rd January 2019) - Stefkó, Dóra; Kúsz, Norbert; Csorba, Attila; Jakab, Gusztáv; Bérdi, Péter; Zupkó, István; Hohmann, Judit; Vasas, Andrea
Abstract: The present study has focused on the isolation and structure determination of phenanthrenes from Juncus atratus Krock. Nine compounds, among them five phenanthrenes, have been isolated from the methanol extract of the plant. Two compounds [juncatrins A (1 ) and B (2 )] are new natural products, three phenanthrenes [juncuenin B (3), effusol (4 ), and dehydroeffusol (5 )], the flavones apigenin (7 ) and luteolin (8 ), the diterpene phytol and 13( R )-hydroxy-octadeca-(9 Z, 11 E, 15 Z )-trien-oic acid (9 ) were isolated for the first time from the plant. Juncatrin A (1 ) is substitued with an acetyl group, while in case of juncatrin B (2 ), an unprecedented acetylene group is connected to the phenanthrene skeleton. The isolated phenanthrenes were evaluated for their antiproliferative activity against HeLa, SiHa and MDA-MB-231 human tumor cell lines. Four phenanthrenes (2, 3, 4 and5 ) were more effective [IC50 s 3.48 μM (2 ), 2.91 (3 ), 3.68 (4 ), and 7.75 μM (5 )] than cisplatin (IC50 12.43 μM) on HeLa cells. Graphical abstract: